Advanced Cell-DEVS modeling applications: a legacy of Norbert Giambiasi. (June 2022) - Wainer, Gabriel A
We describe a number of modeling applications of advanced Cell-DEVS models, a modeling formalism Norbert Giambiasi and I defined in the late 1990s. We discuss improved versions of these models built using the CD++ toolkit, which was built in order to study, model, and simulate such cellular models. The models have removed some limitations that standard cellular models have, which allow each cell to use multiple state variables and multiple ports for inter-cell communications. We show the application of the formalism in three different areas of science and engineering: social models, pedestrian analysis and occupancy in buildings, and virus spreading in computer networks.